The Dilute Phospholipid APTT: A Sensitive Assay for Verification of Lupus Anticoagulants - Alving, Barbara M; Baldwin, Phillip E; Richards, Roberta L; Jackson, Beverly J (Thrombosis and Haemostasis, 1985)
A simple sensitive method for verification of lupus anticoagulants utilizing dilution of phospholipid in the activated partial thromboplastin time (APTT) system is described. Patient plasma, mixed with an equal volume of normal plasma, is activated with micronized silica. To this mixture are added different dilutions of Thrombofax® and then calcium chloride. Clotting times are plotted linearly against the logarithm of the phospholipid dilutions and slopes are calculated by regression analysis. In this assay the mean negative slope of 19 plasmas that contained antiphospholipid activity was five times greater than those of normal plasma or those obtained from patients having single or multiple coagulation factor deficiencies such as those induced by warfarin. The assay can be modified to test heparinized plasmas. Thus, it is a sensitive means by which to verify the presence of lupus anticoagulants in patients who have congenital or acquired factor deficiencies or who are receiving anticoagulant therapy.
Keywords: Lupus anticoagulant; Liposomes; Anti-phospholipid antibodies